PS 16-31 ENDOTHELIN-1 EXAGGERATES TYPE-1 DIABETES-ACCELERATED ATHEROSCLEROSIS THROUGH NADPH OXIDASES 1 AND 4. (September 2016) - Paradis, Pierre; Ouerd, Sofiane; Idris-Khodja, Noureddine; Trindade, Michelle; Coelho, Suellen C.; Jandeleit-Dahm, Karin A.; Schiffrin, Ernesto L.
Abstract : Objective: NADPH oxidase (NOX) 1 but not NOX4-dependent oxidative stress plays a role in diabetic vascular disease, including atherosclerosis. Endothelin (ET)-1 has been implicated in diabetes-induced vascular complications. We showed that crossing mice overexpressing ET-1 selectively in endothelium (eET-1) with apolipoprotein E knockout ( Apoe −/− ) mice exaggerated high-fat diet-induced atherosclerosis in part by increasing oxidative stress. We hypothesized that ET-1 overexpression in the endothelium would exaggerate diabetes-accelerated atherosclerosis through a mechanism involving NOX1 but not NOX4. Design and method: Six-week-old male Apoe −/− mice, eET-1/ Apoe −/− and eET-1/ Apoe −/− mice deficient in Nox1 (eET-1/ Apoe −/− / Nox1 y/− ) or Nox4 (eET-1/ Apoe −/− / Nox4 −/− ) were rendered diabetic with 55 mg/kg/day streptozotocin (STZ) IP for 5 days and studied 14 weeks later. Endothelial function and vascular remodeling were assessed in mesenteric arteries (MA) using pressurized myography. Aortic atherosclerotic lesions were quantified using Oil Red O staining. Results: Diabetic Apoe −/− mice presented an impaired maximal endothelium-dependent vasodilatory response to acetylcholine (21%), which was not observed in diabetic eET-1/ Apoe −/−, eET-1/ Apoe −/− / Nox1 y/− or eET-1/ Apoe −/− / Nox4 −/− mice (99%). Endothelium-independent relaxation to the nitric oxide (NO) donor sodium nitroprusside was similar between groups. Blockade of NO synthase with L-NAME completely blunted endothelium-dependent relaxation to acetylcholine in diabetic eET-1/ Apoe −/− mice, which was prevented by Nox1 but not by Nox4 knockout. ET-1 overexpression caused a 1.8-fold increase in MA media/lumen of diabetic Apoe −/− mice, which was further exaggerated 1.2-fold by Nox4 but not Nox1 knockout. ET-1 overexpression exaggerated > 2-fold the atherosclerotic lesion area in the aortic sinus in diabetic Apoe −/− mice, which was reduced ∼40% by Nox1 and Nox4 knockout. Conclusions: Increased levels of ET-1 exaggerate diabetes-accelerated atherosclerosis through NOX1 and NOX4, despite paradoxically improving endothelium-dependent relaxation in small arteries.